O uso da plataforma adaptativa Khan Academy no ensino de matemática e o impacto nas avaliações - Mognhol, Tiago Delpupo (2015)
This work reports the experience about the use of adaptative Khan Academy platform, avaliable for free at https://pt.khanacademy.org/, with groups of high school juniors in the Integrated Agri-industry Technical Course at Instituto Federal de Educa¸c˜ao, Ciˆencia e Tecnologia do Esp´irito Santo - IFES Campus Venda Nova do Imigrante. In the first term of 2014 we used the traditional teaching methedology; however, in the second term, we decided to evaluate the students according to the results from the platform. Finally, we evaluated the major benefits and differences.